The Principles of Distinguishing Cases in the Russian and Lithuanian Languages (a comparative analysis) - Лихачева, А.Б. (Kalbotyra, 1985)
The article deals with the problem of distinguishing case forms in Russian and Lithuanian from the point of view of the Moscow formal school, based on Fortunatov’s theory. The relations between form and meaning are being investigated in the paper.